The hypoxia‐induced changes in miRNA‐mRNA in RNA‐induced silencing complexes and HIF‐2 induced miRNAs in human endothelial cells. Issue 7 (17th June 2022) - Moszyńska, Adrianna; Jaśkiewicz, Maciej; Serocki, Marcin; Cabaj, Aleksandra; Crossman, David K.; Bartoszewska, Sylwia; Gebert, Magdalena; Dąbrowski, Michał; Collawn, James F.; Bartoszewski, Rafal
Abstract: The cellular adaptive response to hypoxia relies on the expression of hypoxia‐inducible factors (HIFs), HIF‐1 and HIF‐2. HIFs regulate global gene expression changes during hypoxia that are necessary for restoring oxygen homeostasis and promoting cell survival. In the early stages of hypoxia, HIF‐1 is elevated, whereas at the later stages, HIF‐2 becomes the predominant form. What governs the transition between the two HIFs (the HIF switch) and the role of miRNAs in this regulation are not completely clear. Genome‐wide expression studies on the miRNA content of RNA‐induced silencing complexes (RISC) in HUVECs exposed to hypoxia compared to the global miRNA‐Seq analysis revealed very specific differences between these two populations. We analyzed the miRNA and mRNA composition of RISC at 2 h (mainly HIF‐1 driven), 8 h (HIF‐1 and HIF‐2 elevated), and 16 h (mainly HIF‐2 driven) in a gene ontology context. This allowed for determining the direct impact of the miRNAs in modulating the cellular signaling pathways involved in the hypoxic adaptive response. Our results indicate that the miRNA‐mRNA RISC components control the adaptive responses, and this does not always rely on the miRNA transcriptional elevations during hypoxia. Furthermore, we demonstrate that the hypoxic levels of the vast majority of HIF‐1‐dependent miRNAs (including miR‐210‐3p) are also HIF‐2 dependent and that HIF‐2 governs the expression of 11 specific miRNAs. In summary, the switch from HIF‐1 to HIF‐2 during hypoxia provides an important level of miRNA‐driven control in the adaptive pathways in endothelial cells.